Training and innovation among knowledge-based companies in Malaysia - Zulkifli, Izyani (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2012)
Using data from an online survey, this paper attempts to (1) examine the innovative efforts undertaken by knowledge-based companies in Malaysia and (2) to investigate whether or not training has any impact on those innovative efforts. It was found that innovation was evident among the vast majority of the knowledge-based companies, namely, in the “development of a major new product”, an “upgrade of an existing product”, “patents or copyrights for a product” and the “introduction of a new technology that improved production process”. A simple crosstab analysis suggests that when a training policy is in place, it not only positively influences innovation but innovation seems to be more important to the growth of the companies. Additionally, the regression result shows that training has a significant and positive impact on the company’s propensity to innovate.